Design, synthesis, and biological evaluation of 1, 9-diheteroarylnona-1, 3, 6, 8-tetraen-5-ones as a new class of anti-prostate cancer agents. Issue 19 (1st October 2016) - Zhang, Xiaojie; Wang, Rubing; Perez, German Ruiz; Chen, Guanglin; Zhang, Qiang; Zheng, Shilong; Wang, Guangdi; Chen, Qiao-Hong
Graphical abstract: Abstract: In search of more effective chemotherapeutics for the treatment of castration-resistant prostate cancer and inspired by curcumin analogues, twenty five (1 E, 3 E, 6 E, 8 E )-1, 9-diarylnona-1, 3, 6, 8-tetraen-5-ones bearing two identical terminal heteroaromatic rings have been successfully synthesized through Wittig reaction followed by Horner–Wadsworth–Emmons reaction. Twenty-three of them are new compounds. The WST-1 cell proliferation assay was employed to assess their anti-proliferative effects toward both androgen-sensitive and androgen-insensitive human prostate cancer cell lines. Eighteen out of twenty-five synthesized compounds possess significantly improved potency as compared with curcumin. The optimal compound, 78, is 14- to 23-fold more potent than curcumin in inhibiting prostate cancer cell proliferation. It can be concluded from our data that 1, 9-diarylnona-1, 3, 6, 8-tetraen-5-one can serve as a new potential scaffold for the development of anti-prostate cancer agents and that pyridine-4-yls and quinolin-4-yl act as optimal heteroaromatic rings for the enhanced potency of this scaffold. Two of the most potent compounds, 68 and75, effectively suppress PC-3 cell proliferation by activating cell apoptosis and by arresting cell cycle in the G0 /G1 phase.